National differences in incentive compensation practices: The differing roles of financial performance measurement in the United States and the Netherlands - Jansen, E. Pieter; Merchant, Kenneth A.; Van der Stede, Wim A. (Accounting, Organizations and Society, 2009)
This paper describes the findings of a study aimed at providing an international replication of a US-based study by Gibbs et al. [Gibbs, M., Merchant, K., Van der Stede, W., & Vargus, M. (2004). Determinants and effects of subjectivity in incentives. The Accounting Review, 79(2), 409-436; Gibbs, M., Merchant, K., Van der Stede, W., & Vargus, M. (2006). The structure of incentive contracts: Evidence from auto dealerships. Working Paper, University of Chicago, University of Southern California, London School of Economics and University of Texas-Dallas] focused on the incentive compensation practices of firms in the automobile retailing industry. The purpose was to determine the extent to which these practices and their effects were similar across countries. Theory provides conflicting predictions as to whether international practices should reflect a situational "best fit" or "global best practices." We collected a dataset comparable to that of Gibbs et al. from Dutch automobile retailers. The findings reveal dramatic differences in practices across the two countries. As compared to the US firms, the Dutch firms are much less likely to provide their managers with incentive compensation in any form. Where Dutch firms do offer incentive compensation, the payouts are smaller and their bonus awards are less likely to be based on profit measures of performance. But where the Dutch firms use incentive compensation, their performance/reward functions are more complex. Moreover, unlike in the US firms, in the Dutch firms the effects of the use of incentive compensation on net profit and pay satisfaction are negative.